ELECTRONIC MAIL NETWORK SYSTEMS ANALYSIS AT PT.TABITHA EXPRESS JAKARTA - Dedy Kurniady; Irwan Bastian, SKom, MM (Jurnal Sistem Informasi, 1998)
That the electronic mail network system in PT. TABHITA EXPRESS is appropriate, because with the implementation of electronic mail network system efficiency can cut costs as much as possible. So the immediate shortage that occurred at that time implemented an electronic mail network system can be closed, letters, or messages can be received directly at without having to go to the fax machine to retrieve, lost files, the better security because data is always in backup, the cost of fax usage which reduced overseas and many more.